2023
DOI: 10.21203/rs.3.rs-2560733/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolution of barriers to Green Human Resources Management through its drivers in the textile sector of an emerging economy

Abstract: Green HRM is vital in organizations' sustainability policies, seen as a recent research trend. This paper aims to identify the five most important drivers and critical barriers to Green HRM implementation in Pakistan's textile industry. Data were collected from a group of Pakistan's textile industry experts, and the Fuzzy Delphi and Fuzzy AHP methods were used to examine the results. The findings reveal that the most critical five drivers of Green HRM implementation are improvement in company image, maximum us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 108 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Green HRM is linked to promoting pro-environmental behaviors, improving social and economic well-being, and raising awareness about environmental concerns (Miao et al, 2023). It focuses on enhancing company image, maximizing resource utilization, reducing waste, stimulating growth and innovation, and supporting work-life balance to drive environmental sustainability (Miao et al, 2023). Studies have shown that incorporating Green HRM practices can lead to improved employee commitment, which in turn contributes to better sustainable firm performance (DIN, 2023).…”
Section: Goals and Main Principles Of Green Hrm In The Context Of Sus...mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Green HRM is linked to promoting pro-environmental behaviors, improving social and economic well-being, and raising awareness about environmental concerns (Miao et al, 2023). It focuses on enhancing company image, maximizing resource utilization, reducing waste, stimulating growth and innovation, and supporting work-life balance to drive environmental sustainability (Miao et al, 2023). Studies have shown that incorporating Green HRM practices can lead to improved employee commitment, which in turn contributes to better sustainable firm performance (DIN, 2023).…”
Section: Goals and Main Principles Of Green Hrm In The Context Of Sus...mentioning
confidence: 99%
“…These practices not only promote environmental performance but also foster a green organizational culture and encourage environmentally friendly behaviors among employees (Gilal et al, 2019). Critical drivers for successful Green HRM implementation include enhancing company image, maximizing resource utilization, waste reduction, fostering growth and innovation, top management support, and promoting work-life balance (Miao et al, 2023).…”
Section: The Role Of Management In Facilitating Organizational Cultur...mentioning
confidence: 99%
See 3 more Smart Citations